FAKTOR YANG MEMENGARUHI PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT - Trisnawati, Tuti; Priharta, Andry (Taksasila Edukasi Insani, 2024)
This study aims to determine the effect of turnover intentions, time pressure, materiality, review procedures and quality control on premature termination of audit procedures. The research method used is a quantitative method using primary data. The sample determination in this study was taken through auditor data registered in the Directory KAPAP 2021, using the purposive sampling method and the slovin formula so that 90 respondents obtained results. The data obtained is then processed using IBM SPSS version 26 software using a statistical test tool, namely multiple regression analysis. The results of this study indicate that: (1) turnover intentions have a significant effect on premature termination of audit procedures; (2) time pressure has a significant effect on premature termination of audit procedures; (3) materiality has a significant effect on premature termination of audit procedures; (4) review and quality control procedures have a significant effect on premature termination of audit procedures; (5) turnover intentions, time pressure, materiality, review procedures and quality control simultaneously have a significant effect on premature termination of audit procedures. Keywords: Turnover Intentions, Time Pressure, Materiality, Quality Control and Review Procedures, Premature Sign-off of Audit Procedures